2020
DOI: 10.1002/qua.26249
|View full text |Cite
|
Sign up to set email alerts
|

Reagent addition sequence and equivalent in N‐heterocyclic carbene‐catalyzed nonpolar inversion enable conversion from aldimine to benzoxazole

Abstract: The umpolung reaction catalyzed by N-heterocyclic carbenes (NHCs) has been widely studied and well recognized, but their role in the nonpolar inversion reaction under oxidative condition has been rarely reported. In this paper, the mechanism of the oxidative nonpolar inversion reaction catalyzed by NHCs to produce benzoxazole is investigated in detail. The reaction occurs through five processes. For oxidation in the second process, two successive tautomerizations followed by oxidation are energetically more fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The diverse carbene-related transformations highlight the indispensable role of carbene in organic synthesis, which also implies that the contributions from computational studies are highly appreciated. , Previous computational studies of metal carbene-mediated X–H insertion (X = C, N, O, etc. ) and olefin metathesis have shown that theoretical calculations can enable a better mechanistic understanding of carbene chemistry. A summary of recent advances in theoretical studies would provide critical guidance for metal carbene formation and enlighten the rational design of new metal carbene transformation reactions. This account mainly focuses on our recent computational studies of the transition-metal-catalyzed carbene transformation with nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse carbene-related transformations highlight the indispensable role of carbene in organic synthesis, which also implies that the contributions from computational studies are highly appreciated. , Previous computational studies of metal carbene-mediated X–H insertion (X = C, N, O, etc. ) and olefin metathesis have shown that theoretical calculations can enable a better mechanistic understanding of carbene chemistry. A summary of recent advances in theoretical studies would provide critical guidance for metal carbene formation and enlighten the rational design of new metal carbene transformation reactions. This account mainly focuses on our recent computational studies of the transition-metal-catalyzed carbene transformation with nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an in-depth DFT study was conducted relative to this catalytic cycle, in order to substantiate it by verification of both rationality and feasibility (Scheme 22). [41] Scheme 19. Detailed mechanism for NHC-catalyzed oxidative acetalization of benzoic acid.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Recently, an in‐depth DFT study was conducted relative to this catalytic cycle, in order to substantiate it by verification of both rationality and feasibility (Scheme 22 ). [41] …”
Section: Acyl/imidoyl Azolium Intermediatesmentioning
confidence: 99%